Best practices and use of technology in one-person libraries of language and cultural centers in Metro Manila towards proposing a technology manual for one person librarians - Cruz, Roy Alvin R. (School of Library and Information Studies, University of the Philippines, Diliman, 2014)
"One-person librarianship is a specialized form of small librarianship wherein all professional work in a library is managed by a single professional librarian. The tasks this individual does include the littlest of day-to-day routines to the most crucial decision-making processes that can define either the success or failure of his or her library. One important aspect of investigation in this study are the technologies that the librarians use which help them in doing their duties well albeit being alone. This study uncovers the current state of one-person libraries in foreign language and cultural centers in Metro Manila in terms of the technical, user, and information technology-based services that they provide; and the current technologies used by the solo librarians that aid them in performing their duties in the language center libraries. All foreign language and cultural centers in Metro Manila that maintain a library make up the population for this study. This includes Alliance Francaise de Manille, Instituto Cervantes de Manila, Goethe-Institut Philippinen, Japan Foundation Manila, Korean Cultural Center in the Philippines, and Societa Dante Alighieri Comitato di Manila. The face-to-face interview method was used in collecting data so the one-person librarians could easily answer open-ended questions. The ASLP Standards for Special Libraries in the Philippines was also used as guide in analyzing the services of the libraries. The data gathered from the interviews were used to create a ''best practices manual'' of the recommended technologies to help one-person librarians on their technology-related decisions. The results show that one-person librarians could handle a library having as much as 26,0o00 materials as long as they are equipped with the proper technologies. Cataloging and classification and collection development are the technical services being done by the one-person librarians. In terms of readers services, circulation, research support, and library marketing are the services needed by their patrons. It was found that an Integrated Library System (ILS) is one of the most important technologies for the one-person librarians. It acts as their virtual assistant in doing library services like cataloging, circulation, and providing public catalog for users. Maintaining websites and social media presence was also found to be important functions of one-person librarians at the language center libraries. A best practices manual is created at the end of this study summarizing the best practices of recommended technologies for one-person librarians. For further studies, it is recommended that other potential technologies not yet used on one-person libraries be studied that may be of help to the librarians such as RFIDs and mobile applications."